Adoption of the Guidelines for Higher Education Libraries in Portugal: contributions to assessment - Sanches, Tatiana (2020)
Three years after the publication and large-scale dissemination of the guideline document "Recommendations for Higher Education Libraries", we seek to understand the extent to which this document has been adopted by librarians and how practices and experiences have been introduced in Portuguese higher education libraries. This paper aims to assess the application of the Recommendations on user training, particularly in information literacy; in digital content management, including data and scientific production; and in the direct support to students, teachers and researchers, not forgetting topics of space management and information resources as a whole. For this purpose, a questionnaire survey was used for higher education libraries in Portugal. The most implemented areas are information literacy and the management of institutional repositories, and support for editorial projects was the one with the lowest level of application.